2003
DOI: 10.1097/01.shk.0000048899.46342.f6
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteases Are Involved in the Pathogenesis of Trauma-Hemorrhagic Shock-Induced Gut and Lung Injury

Abstract: The objective of this work was to test the hypothesis that Intraluminal serine proteases are involved in trauma-hemorrhagic shock (T/HS)-induced intestinal and lung injury. Male Sprague-Dawley rats were administrated the serine protease inhibitor (6-amidino-2-naphthyl p-guanidinobenzoate dimethanesulfate, Nafamostat) either intraluminally into the gut or intravenously after a laparotomy (trauma) and then subjected to 90 min of hemorrhagic shock (T/HS) or sham shock (T/SS). Intestinal and lung injury was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 28 publications
2
65
0
1
Order By: Relevance
“…It has been observed that plasma from male rats subjected to trauma-hemorrhage primes neutrophil respiratory burst, but plasma from proestrus females subjected to traumahemorrhage does not (79). Intraluminal nafamostat (serine protease inhibitor) reduced trauma-hemorrhage-induced gut and lung injury as well as neutrophilactivating ability, demonstrating that neutrophil-derived serine proteases play an important role in traumahemorrhage-induced gut and lung injury (80). Ischemic gut is a major source of factors that lead to neutrophil activation (81).…”
Section: Neutrophilsmentioning
confidence: 99%
“…It has been observed that plasma from male rats subjected to trauma-hemorrhage primes neutrophil respiratory burst, but plasma from proestrus females subjected to traumahemorrhage does not (79). Intraluminal nafamostat (serine protease inhibitor) reduced trauma-hemorrhage-induced gut and lung injury as well as neutrophilactivating ability, demonstrating that neutrophil-derived serine proteases play an important role in traumahemorrhage-induced gut and lung injury (80). Ischemic gut is a major source of factors that lead to neutrophil activation (81).…”
Section: Neutrophilsmentioning
confidence: 99%
“…The production of inflammatory mediators in mesenteric I/R can be inhibited by blockade of digestive proteases in the lumen of the intestine, a procedure that attenuates many symptoms of experimental shock. 1,10,40,41,57,58 Inflammatory mediators are readily produced in vitro from intestinal tissue in the presence of digestive enzymes, among which pancreatic trypsin serves as a particularly potent producer of mediators for leukocyte activation. 13 The inflammatory mediators produced by proteolytic digestion of the intestinal wall consist of both peptide and lipid components, many of which with molecular weight below 10 kd.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have largely focused on the splanchnic circulation and systemic host factors because it is well recognized that shock or major trauma leads to a decrease in mesenteric perfusion, resulting in an ischemia-reperfusion injury as well as an ischemia-reperfusion-induced gut inflammatory response (1). This work has led to the recognition of the important roles of inflammatory cells, proinflammatory molecules, intraluminal proteases, reactive oxygen species (ROS), and reactive nitrogen intermediates (RNI) in the pathogenesis of ischemiareperfusion-related gut injury and dysfunction (1,7,8,13,15,22). However, very little attention has been paid to the role of the unstirred mucus layer as a critical component of the gut barrier or the consequences of damage to this mucus layer.…”
mentioning
confidence: 99%